Cognitive impairment and dependency in activities of daily living: a cross-lagged analysis - Fu, Xuewei; Ji, Shuming; Li, Jiafeng; Chen, Ting; Liu, Xuhuan; Kuang, Weihong (Frontiers in Aging Neuroscience, 2025)
BackgroundThis study investigates the bidirectional relationship between cognitive function and Activities of Daily Living (ADL) at varying levels of cognitive impairment. Specifically, it explores how cognitive function affects Basic Activities of Daily Living (BADL) and Instrumental Activities of Daily Living (IADL) over time, and how changes in ADL impact cognitive function.MethodA retrospective analysis of clinical data was conducted using cross-lagged panel models to examine the relationships between cognitive function and ADL. Cognitive function was measured using the Montreal Cognitive Assessment, while ADL were assessed via standardized measures of both BADL and IADL at two time points. Participants were grouped according to the severity of their initial cognitive impairment, allowing for comparative analysis across different levels of impairment.ResultsCross-lagged analyses revealed that lower baseline cognitive function was significantly associated with increased ADL dependency at follow-up (β = −0.302, p < 0.001), with a stronger association for IADL (β = −0.318, p < 0.001) than for BADL (β = −0.274, p < 0.001). Subgroup analyses indicated that these associations were most pronounced in individuals with moderate cognitive impairment.ConclusionThis study highlights the significant association between cognitive function and ADL, with lower baseline cognitive function predicting increased dependency, particularly in IADL. The findings emphasize the importance of early cognitive health interventions to prevent further decline in daily functioning, especially in individuals with moderate cognitive impairment.